(18F)Fluorodeoxyglucose positron emission tomography for detection of bone marrow involvement in children and adolescents with Hodgkin's lymphoma - Purz, Sandra; Mauz-Körholz, Christine; Körholz, Dieter; Hasenclever, Dirk; Krauße, Antje; Sorge, Ina; Ruschke, Kathrin; Stiefel, Martina; Amthauer, Holger; Schober, Otmar; Kranert, W. Tilman; Weber, Wolfgang Andreas; et al. (Journal of clinical oncology, 2011)
PURPOSE: Currently, a routine bone marrow biopsy (BMB) is performed to detect bone marrow (BM) involvement in pediatric Hodgkin's lymphoma (HL) stage greater than IIA. [(18)F]fluorodeoxyglucose positron emission tomography (FDG-PET) is increasingly used for the initial staging of HL. The value of using FDG-PET to detect BM involvement has not been sufficiently defined. We compared the results of BMBs and FDG-PET for the diagnosis of BM involvement in a large pediatric group with HL. - PATIENTS AND METHODS: The initial staging of 175 pediatric patients with newly diagnosed classical HL stage greater than IIA was determined by using BMB, FDG-PET, chest computed tomography (CT), and magnetic resonance imaging (MRI) or CT of the neck, abdomen, and pelvis. Staging images were prospectively evaluated by a central review board. Skeletal regions that were suggestive of BM involvement by either method were re-evaluated by using different imaging modalities. In suspicious cases, bone scintigraphy was performed. If follow-up FDG-PET scans were available, the remission of skeletal lesions during treatment was evaluated. - RESULTS: BMB results were positive in seven of 175 patients and were identified by FDG-PET. FDG-PET scans showed BM involvement in 45 patients. In addition, the lesions of 32 of these 45 patients had a typical multifocal pattern. In 38 of 39 follow-up positron emission tomography scans, most of the skeletal lesions disappeared after chemotherapy. There was no patient with skeletal findings suggestive of BM involvement by MRI or CT with a negative FDG-PET. - CONCLUSION: FDG-PET is a sensitive and specific method for the detection of BM involvement in pediatric HL. The sensitivity of a BMB appears compromised by the focal pattern of BM involvement. Thus, FDG-PET may safely be substituted for a BMB in routine staging procedures.